Emergence of Porcine Circovirus 2 Associated Reproductive Failure in Southern India. Issue 3 (15th September 2014) - Karuppannan, A. K.; Ramesh, A.; Reddy, Y. K.; Ramesh, S.; Mahaprabhu, R.; Jaisree, S.; Roy, P.; Sridhar, R.; Pazhanivel, N.; Sakthivelan, S. M.; Sreekumar, C.; Murugan, M.; et al.
Summary: Incidence of unusually high numbers of stillbirths was observed at a piggery unit at the Veterinary University research farm in Tamil Nadu State of India. Systematic examination of the tissue from stillborn piglets led to the identification of presence of Porcine circovirus 2 (PCV2). Detailed analysis utilizing electron microscopy, polymerase chain reaction and sequencing confirmed the presence of PCV2 in the tissue of affected piglets. Histopathology analysis of the affected piglet tissue showed lymphoid cell depletion of lymphnodes, spleen and infiltration of liver, kidney, myocardium, etc. Retrospective examination of the morbidity and mortality history in the farm revealed high mortality in young and weanling piglets suggestive of PCV2 infection‐induced diseases. This is the first report of emergence of major disease incidence in farmed swine due to PCV2 infection in India.